Type A, Or Type B, That Is The Question; A Critical Examination Of Productoriented And Process-oriented Syllabuses In Foreign Language Learning And Teaching - Abla Benbellal (The Journal of Studies in Language, Culture and Society)
The current paper aims at examining and comparing two major syllabus types, Type „A‟ and Type „B‟, by reviewing the literature on three product-oriented (type A) syllabus sub-types namely: structural, notional-functional and situational syllabuses and three process-oriented (type B) syllabus sub-types notably task-based, process and content-based syllabuses. The discussion focuses on the characteristics of both types, the different views of language and language learning that influenced the classification of the two syllabus types as well as the benefits and drawbacks of each type in foreign language learning and teaching. At the end of the paper, foreign language teachers are invited to adopt the eclectic approach by combining both syllabus types. This combination will, therefore, help in counteracting the weaknesses of both types and provide teachers with opportunities to address their learners‟ diverse needs and meet their expectations.